If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 9y = 27solvey Solving 3x + 9y = 27elosvy Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9y' to each side of the equation. 3x + 9y + -9y = 27elosvy + -9y Combine like terms: 9y + -9y = 0 3x + 0 = 27elosvy + -9y 3x = 27elosvy + -9y Divide each side by '3'. x = 9elosvy + -3y Simplifying x = 9elosvy + -3y
| 11.2=v/7 | | 10x-12x=20 | | 17v=9v+48 | | x^3-10x^2+17x-8=0 | | 4x-7=2y+5 | | 15x+10=6x+298 | | -5-15y+1=2(7y-16)-y | | X-1/6=7/12 | | 10x-12x-8=12 | | 3x-2=2x(-6) | | -114q=-1176-16q | | A=18W-W^2 | | ix-3x=0 | | 2(x-4)=3x-9-x | | y-2=4/5(x-3) | | (2x-1)(5x-5)= | | 4r-4=(r-4)(r-4) | | 0.6x-1.9y+3.2=0 | | 160=3x+y | | -9y+19=4y-7 | | 1-4.9x^2=0 | | (w-4)/4w=1/5 | | 12y-7+1+4y= | | ix=3x | | 7-2y=10-6y+4y | | x(x-3)=16/3 | | -3(5u-2)+5u=4(u+4) | | 3(4y)=24 | | 6(x-3)=9x-24 | | 2(6d+3)=18-48+9d | | X+(x-5)=20 | | 10.2u+0.5=2.5u-0.3(u-7) |